Pengaruh Konflik dan Stres Kerja terhadap Kinerja Pegawai di Badan Pengawas Pemilihan Umum (Bawaslu) Kabupaten Batang Hari Jambi - AZ, Siti Marlina; Siswati, Etty; Ratna, Ratna; Khoiroh, Nadiatul; Mustina, Yulia (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of work conflict and work stress on employee performance at Bawaslu Batang Hari Regency. The population of the study was all 112 Bawaslu employees of Batanghari Regency with a sample of 45 people with respondent characteristics of gender, age, length of service and education. The analysis method used was a quantitative method with analytical tools of validity and reliability tests as well as multiple linear regression, t-test, F-test and determination test. The results of the study concluded that there was a significant influence between conflict variables and work stress on employee performance with a contribution of 24.5%, but partially there was no significant influence between work stress variables on employee performance at Bawaslu Batang Hari Regency.